Bilateral adrenal haemorrhage complicated by sepsis, coagulopathy, influenza A and adrenal crisis. Issue 12 (28th December 2020) - Mulvihill, Eanna; Gannon, Martin; Balasubramaniam, Ananthapadmanaban; Fitzpatrick, John
Abstract : Bilateral adrenal haemorrhage is a rare and often fatal condition that most commonly occurs under conditions of severe physiological stress. We describe a 33-year-old male patient with ulcerative colitis who presented with acute worsening epigastric pain, vomiting and raised inflammatory markers. Initial differentials included gastritis and peptic ulceration. Gastroscopy revealed no abnormalities. By day 3, he had developed sepsis with a sequential organ failure assessment score of 2 as well as coagulopathy. A subsequent CT scan diagnosed bilateral adrenal haemorrhage. A short Synacthen Test confirmed adrenal insufficiency and he was treated with replacement steroids and antibiotics for a possible urinary tract infection or pyelonephritis and he recovered well. Several days later he developed fever, dyspnoea and a productive cough. Subsequently, he became hypotensive (Blood Pressure (BP) 95/65 mm Hg) and unresponsive with a Glasgow Coma Scale of 7 and was hyponatraemic and hyperkalaemic. He was intubated and transferred to a tertiary hospital for intensive care unit management where investigations confirmed the patient to be influenza A positive.